The Practice of Interactive Multimedia to Improve Students Procedure Text Learning - Izzah, Nurul; Ammade, Salasiah; Nur, Rafi'ah; Latifa, Ammang; Hajar, Siti (BABASAL English Education Journal, 2024)
In the era of technology-based education, it is crucial to understand the effectiveness of interactive media in enhancing students' comprehension of specific text types. This study aims to examine the practice of interactive media to student learning outcomes at SMP IT Wahdah Islamiyah Makassar regarding Procedure texts. The subjects in this study are 20 students of IX B1 Class. This study used pre-experimental/one-shot case study research to compare learning outcomes. The data collection method is the academic performance outcomes of the students and field notes analyzed quantitatively. The findings showed significant differences in student understanding when receiving instruction with interactive multimedia then before. Students after taught using interactive multimedia show a higher level of understanding of the Procedural Text. Therefore, the use of interactive multimedia in the teaching of Procedure Texts is highly recommended as it significantly improves students' understanding and is well received by students. Although the integration of interactive multimedia in the classroom is increasing, there is still a gap in understanding its specific impact on student learning outcomes for Procedural Texts.